FED CORBETT Century of Enslavement: The History of The Federal Reserve - corbettreport (2014)
TRANSCRIPT AND RESOURCES: http://www.corbettreport.com/federalr... What is the Federal Reserve system? How did it come into existence? Is it part of the federal government? How does it create money? Why is the publi